Insulin-like growth factor 2 promotes osteoclastogenesis increasing inflammatory cytokine levels under hypoxia - Takao Kondo; Hiromasa Aoki; Yuto Otsuka; Yohei Kawaguchi; Yuko Waguri-Nagaya; Mineyoshi Aoyama (Elsevier, 2022)
Osteoporosis is caused by an imbalance in bone remodeling due to abnormal osteoclast (OC) formation and activation. Hypoxia at the site of inflammation promotes OC formation and activation in various species, including humans. We previously reported that insulin-like growth factor 2 (IGF2) plays an important role in osteoclastogenesis under hypoxia. In our present study, we focused on the mechanism of osteoclastogenesis in regard to IGF2 signaling under hypoxia. We confirmed that the addition of IGF2 promoted osteoclastogenesis under normoxic conditions. Conversely, IGF2-neutralizing antibodies inhibited osteoclastogenesis under both normoxic and hypoxic conditions. IGF2 addition increased levels of phosphorylated Akt (Thr308 and Ser473) and NF-κB (Ser536), indicating activation of the Akt-NF-κB pathway. IGF2 also increased the expression of inducible nitric oxide synthase, which promotes osteoclastogenesis via nitric oxide production. Expression levels of genes encoding inflammatory cytokines, such as tumor necrosis factor-α, interleukin (IL)-1β, and IL-6, were upregulated, indicating that IGF2 promotes osteoclastogenesis by increasing the expression of inflammatory cytokines via activation of the Akt-NF-κB pathway. These results suggest that IGF2 is a promising therapeutic target for osteoporosis and rheumatoid arthritis.